Pengembangan Bahan Ajar Berbentuk Komik Pada Matapeljaran IPS Materi Kelas IV SDN 1 Jerowaru - Lalu. A. Hery Qusyairi (Al-Faiza : Journal of Islamic Education Studies, 2024)
Learning media is one component in education that helps determine success in the learning process. So for educators, it is necessary to understand the use of learning media by adjusting the material to be taught. This study aims to develop and determine how students respond to comic-based teaching materials in the social studies subject matter of jobs around me in grade IV of SDN 1 Jerowaru. This type of research is a development using the Borg and Gall model which has been simplified into 7 stages, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trial, and 7) product revision. Based on the results of validation by media experts, language experts and education practitioner experts, the results of media validation with an actual score of 34 were categorized as "good", the results of validation by language experts with an actual score of 20 were categorized as "good" and the results of validation by education practitioner experts with an actual score of 42 were categorized as "good", and the results of the student evaluation test were declared complete with a completeness value of 100% and KKM 65 with an average of 81% and the results of student responses from 20 students received an assessment of 100%. Based on these results, the comic-based teaching material product for the social studies subject on the work around me material for grade IV of SDN Jerowaru is suitable for use in the learning process.